Government policy transformation toward a reformed rental housing ecosystem as a mitigator of homelessness in postpandemic India - Datta U.; Raman R. (My University, 2025)
This research paper provides a comprehensive examination of rental housing as a potential strategy for mitigating homelessness in India. With a population exceeding 1.3 billion and substantial socioeconomic disparities, India grapples with a pronounced housing crisis, with an estimated 1.77 million homeless as per Census 2011. Amidst this landscape, the study identifies rental housing as an underexplored yet potent tool to address homelessness. The research adopts a mixed-method approach, drawing from a comprehensive review of government policies, international case studies, and academic literature on rental housing and homelessness. The evolution of rental housing policies in India is critically analyzed, including the Rent Control Act (1948), the National Urban Housing and Habitat Policy (2007), and the Draft Model Tenancy Act (2020). Concurrently, international best practices in rental housing policies are explored through case studies from Germany, Singapore, and the United States. The study puts forth a set of policy recommendations for India, encompassing potential policy changes, promotion of vacant housing stock, targeted measures for migrant workers, participation models for the private sector, and fostering innovation in rental housing design. The paper also advocates strengthening the informal rental housing sector and developing rent subsidy programs. The implications of the study underscore the necessity of a multifaceted approach in rental housing policy and practice for mitigating homelessness in India. The paper concludes by identifying future research directions, stressing the importance of contextual, innovative, and inclusive strategies in India's rental housing policy formulation. The paper contributes to the body of knowledge by establishing a link between rental housing policies and homelessness and suggesting actionable policy measures for India. © 2024 Elsevier Inc. All rights are reserved.